2015
DOI: 10.1007/s00109-015-1283-1
|View full text |Cite
|
Sign up to set email alerts
|

Berberine inhibits Smad and non-Smad signaling cascades and enhances autophagy against pulmonary fibrosis

Abstract: Berberine inhibits Smad 2/3 activation and enhances Smad 7 in bleomycin-induced rat lungs. Bleomycin-induced activation of FAK is inhibited by berberine. Berberine inhibits bleomycin-induced activation of PI3K/Akt cascade. Berberine inhibits mTOR activation to enhance autophagy and suppresses fibrotic markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 34 publications
2
60
0
Order By: Relevance
“…More recently, it was reported that BBR could alleviate high glucose-induced podocyte apoptosis via autophagy 15 . In addition, BBR can stimulate autophagy in various tissues including heart 16 , lungs 17 and hepar 18 , however, this has not been shown in the NP. Considering that oxidative stress, apoptosis and inflammatory activation are all elements of IVDD pathology, we hypothesize that BBR may utilize autophagy to prevent the formation of IVDD.…”
Section: Introductionmentioning
confidence: 92%
“…More recently, it was reported that BBR could alleviate high glucose-induced podocyte apoptosis via autophagy 15 . In addition, BBR can stimulate autophagy in various tissues including heart 16 , lungs 17 and hepar 18 , however, this has not been shown in the NP. Considering that oxidative stress, apoptosis and inflammatory activation are all elements of IVDD pathology, we hypothesize that BBR may utilize autophagy to prevent the formation of IVDD.…”
Section: Introductionmentioning
confidence: 92%
“…16,17 All rats were sutured with amikacin lotion at the neck suture 3 days post-operation. Rats were divided into different groups: normal group (15 normal rats), control group (30 rats injected with saline), and BLM group (110 rats injected with 40 mg/kg sodium pentobarbital).…”
Section: Animal Treatmentmentioning
confidence: 99%
“…Researchers have proved that C. sinensis can ameliorate fibrosis in the liver, pulmonary and kidney through inhibition of TGF-b1 expression and promotion of collagen degradation. 14,15 The growth of C. sinensis natural fungus is unusual owing to its limited ability to grow on Tibetan plateau and southwestern China. Hence, Hirsutella sinensis culturing in vitro became an attractive substitute for the preparation of health supplements.…”
Section: Introductionmentioning
confidence: 99%